2005
DOI: 10.1002/ps.1010
|View full text |Cite
|
Sign up to set email alerts
|

Control of blue mold (Penicillium expansum) by fludioxonil in apples (cv Empire) under controlled atmosphere and cold storage conditions

Abstract: A reduced risk fungicide, fludioxonil, was tested for its efficacy against blue mold caused by thiabendazole-resistant and -sensitive Penicillium expansum (Link) Thom in apples under three storage conditions. In a co-treatment, fludioxonil and inoculum were applied together to test the protective activity of the fungicide on wounds that had been aged for 1 or 2 days. The fungicide was also tested for its curative activity in post-inoculation treatment on apples that had been inoculated for 1 or 2 days. Fludiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Because of extensive use of most common fungicides (i.e. thiabendazole), P. expansum has become resistant to them and thus they have become ineVective (Errampalli et al, 2005). We observed that after CA cold storage, fungicide treatment was only eVective in ripe apples and that after further storage at 20°C; lesion diameter was only signiWcantly bigger for ripe untreated apples.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because of extensive use of most common fungicides (i.e. thiabendazole), P. expansum has become resistant to them and thus they have become ineVective (Errampalli et al, 2005). We observed that after CA cold storage, fungicide treatment was only eVective in ripe apples and that after further storage at 20°C; lesion diameter was only signiWcantly bigger for ripe untreated apples.…”
Section: Discussionmentioning
confidence: 89%
“…Following harvest and before CA storage, a post-harvest drench application of thiabendazole has been used to control storage rots of apples (Errampalli, Northover, Skog, Brubacher, & Collucci, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The phenylpyrroles are derived from the antibiotic pyrrolnitrin, which is produced by many Pseudomonas sp. Errampalli, Northover, Skog, Brubacher, and Collucci (2005) showed that fludioxonil controlled blue mould caused by thiabendazole-resistant P. expansum under three different storage conditions (20°C, 4°C and 1°C). However, Iacomi-Vasilescu et al (2004) reported field resistance to fludioxonil in Alternaria spp.…”
Section: Use Of Post-harvest Fungicidesmentioning
confidence: 99%
“…This study confirms the additive effect of applying fungicides with that of storage under refrigeration and controlled atmosphere. Errampali (2004) & Errampali et al (2005 used the fungicide fludioxinil both as a preventative treatment and in the treatment of apples already infected with P. expansum. According to Neri et al (2006), vapours of trans-2-hexenal (an aroma component of many fruits and vegetables), with a concentration of 12.5 lgL/L showed a potential for the control of blue rot, the PAT content and apple quality in Golden Delicious apples.…”
Section: Fruit Storagementioning
confidence: 99%